Human Resource Management Strategy in Improving Employee Performance at ICTC Tutoring Center in Tanjungpinang City - Fernando Alexsander; Ferdi Stefiano; Ivanny Gracia Hondo; Alfian Fazar Ramadhan; Satriadi Satriadi (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study discusses the human resource management (HR) strategies implemented at ICTC Tutoring in Tanjungpinang City to improve employee performance. This study uses a qualitative approach with data collection techniques through direct observation and interviews with senior officials at ICTC Tutoring. The data analysis used descriptive analysis. The results of this study describe a proactive recruitment process that ensures that quality candidates are selected, while training and mentoring programs support the development of employee skills and motivation. In addition, retention strategies that focus on employee satisfaction and well-being help create a positive work environment. By implementing these strategies, it is hoped that ICTC can improve the quality of educational services and meet the expectations of students and parents, while maintaining its position as a superior educational institution in Tanjungpinang City.